Digitized Presence: Refracted Spiritual Realities in Contemporary Nigeria - Ndidi Justice Gbule; Patrick Eluke (Khazanah Journal of Religion and Technology, 2026)
Presence has often been tied to physical proximity. In contemporary Nigerian Christianity, however, this assumption is increasingly difficult to sustain. This paper argues that digital mediation does not simply extend worship into virtual space; it reconfigures what counts as spiritual presence in the first place. Existing scholarship tends to treat media as channels of transmission or as sites of hybrid practice. While useful, such approaches do not go far enough. They leave largely unexamined the question of how presence itself is being reconstituted. Drawing on interpretive engagement with livestream services, WhatsApp prayer exchanges, and social media devotional practices, the paper develops the concept of refracted spiritual presence. The argument is that digital platforms do not merely carry religious content; they reshape the conditions under which presence is recognized, experienced, and authorized. In this setting, participation no longer depends on co-location. Acts such as typing “Amen,” sharing prayer messages, or joining a livestream become part of a wider field of mediated yet effective religious practice. At the same time, this transformation is not without tension. The increased circulation of spiritual content raises questions about commodification, visibility, and the shifting grounds of authority. What emerges is not the disappearance of presence, but its redistribution across interfaces, interactions, and everyday digital routines.